2015
DOI: 10.1016/j.rmed.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

6-Min walk-test data in severe obstructive-sleep-apnea-hypopnea-syndrome (OSAHS) under continuous-positive-airway-pressure (CPAP) treatment

Abstract: Severe OSAHS may play a role in reducing the functional capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Assessment of submaximal exercise capacity in individuals with OSA is found in the literature mainly in studies employing the 6MWT, highlighting potential exercise intolerance accompanied by abnormal cardiovascular responses in this population, 7 , 8 even after CPAP treatment, with similar results to those of CPET, as well as a reduction in 6MWD when compared with the optimal 6MWD. 9 , 10 Another field test that has been used in this population is the shuttle test, which was able to detect changes in FEC after CPAP treatment, as well as weight reduction and excessive daytime sleepiness. 26 To our knowledge, there have been no studies on the use of the 6MST for assessing individuals with OSA treated with CPAP.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of submaximal exercise capacity in individuals with OSA is found in the literature mainly in studies employing the 6MWT, highlighting potential exercise intolerance accompanied by abnormal cardiovascular responses in this population, 7 , 8 even after CPAP treatment, with similar results to those of CPET, as well as a reduction in 6MWD when compared with the optimal 6MWD. 9 , 10 Another field test that has been used in this population is the shuttle test, which was able to detect changes in FEC after CPAP treatment, as well as weight reduction and excessive daytime sleepiness. 26 To our knowledge, there have been no studies on the use of the 6MST for assessing individuals with OSA treated with CPAP.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies one-third of the subjects reported experiencing dyspnea during the 6MWT while others did not. 80,81 With that said, the occurrence of dyspnea during exercise in people with OSA is not at all a new finding. 51,80,82 The highest number of events occurred while untrained and immediate-post.…”
Section: Dyspneamentioning
confidence: 99%
“…80,81 With that said, the occurrence of dyspnea during exercise in people with OSA is not at all a new finding. 51,80,82 The highest number of events occurred while untrained and immediate-post. Dyspnea upon maximal effort has been previously noted in several studies pertaining to people with OSA.…”
Section: Dyspneamentioning
confidence: 99%
“…Clinical data were collected using the ATS questionnaire [28], widely described elsewhere [8, 10, 24]. Parity, defined as the number of offspring a female has borne, was introduced in three forms: numerical (unit), two groups [G 1 (parity ≤ 6); G 2 (parity > 6)] and three classes [C 1 : 1 ≤ parity ≤ 4; C 2 : 5 ≤ parity ≤ 8; C 3 : parity ≥ 9] [17, 2931]. Menopausal status was determined using the stages of reproductive aging workshop classification [32].…”
Section: Population and Methodsmentioning
confidence: 99%